Mensuraç\~ao dos gastos tributários em saúde: 2003-2006 - Carlos Octávio Ocké-Reis; Fausto Pereira dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This technical paper estimates the deductions on tax credits in Brazil for health care during 2003 and 2006. Subsidies for private health insurance are the focus of this study. It seems to be a contradiction between the redistribution model in the Constitution and the level of public spending on health care in Brazil. For this reason, one could argue that tax subsidies deprive the Unified Health System (Sistema Único de Saúde, or SUS) of the financial resources that might otherwise have been used to improve its accessibility and quality, especially under fiscal constraint.
Keywords: H2; I11; I18; 330